Thioether-triphenolate bimetallic iron(iii) complexes as robust and highly efficient catalysts for cycloaddition of carbon dioxide to epoxides. (24th September 2015) - Buonerba, Antonio; Della Monica, Francesco; De Nisi, Assunta; Luciano, Ermanno; Milione, Stefano; Grassi, Alfonso; Capacchione, Carmine; Rieger, Bernhard
Abstract : The selective and effective synthesis of organic carbonates under mild conditions, starting from carbon dioxide and oxiranes, catalyzed by metal complexes is currently a focus of interest for both industrial and academic researchers. We recently developed a novel thioether-triphenolate iron(iii ) catalyst (C t -Bu ) that has proven to be highly active for the coupling of CO2 with epoxides, resulting in cyclic organic carbonates under solvent-free conditions. In the current work, the properties of this novel class of catalysts were extensively investigated. In particular, the steric properties of the ligand were modulated by changing the substituents of the aromatic rings in order to obtain a deeper knowledge of the relationship between the complex structure and catalytic performance/selectivity for these iron complexes. Notably, the less steric demanding iron(iii )CH complex synthesized shows, when activated by n -tetrabutylammonium bromide, an impressive turnover frequency (TOF) of 3800 h −1 for the formation of propylene carbonate and glycerol carbonate which are, by far, the highest reported for an iron based catalyst and compares well with the most active catalyst based on other metals.